ISLAMIC EDUCATIONAL PATTERN AND STREET CHILDREN CARE - uddin, Hasan (Studia Religia, 2018)
AbstractThis reseach aimed to determine the background of the emergence of streetchildren stayed Puri Indah shelter house of Sidoarjo. In addition, this reseachalso aimed to determine the pattern of communication that is formed, thesteps of assistance and the factors driving and inhibiting the implementation ofstreet child educational pattern. Qualitative descriptive research was done bycollecting data using interviews, observation, literature study and documents.The informant was chosen by using purposive sampling. Analytical techniquesused interactive analysis model which includes data collection, data reduction,data presentation and conclusion. From the research results could be seenthat the cause of the emergence of street children because of economic factors,family disorganization, street family dynasties and customs tangent with streetchildren. Responding to this Puri Indah shelter house of Sidoarjo madeeducation pattern to street children. The communication pattern formed inthis program is the formal communication seen at the time of routine learningand field study, non-formal communication seen in activity outside schooland is more relaxed. Non verbal communication seen from the response oflimbs of students. In connection with the interaction, there emerged a linearcommunication model, transactional and intransactional. The Puri Indahshelter house of Sidoarjo has innovative teaching methods both conductedby teachers and involving the active role of students. In order for our programto be more qualified, Puri Indah shelter house of Sidoarjo provided variousfacilities for students such as supporting books, bicycle, stationery library andpaying attention to their nutrition. Nevertheless there was no doubt there weresome weaknesses such as the arrogant nature of the students, the credibilityof teachers who had not maximized, the limited facilities of infrastructure.However it could be overcome with the spirit of all elements and support ofall parties.Â Keywords: Education, Parenting, Street Children